2014
DOI: 10.1158/1055-9965.epi-13-1130
|View full text |Cite
|
Sign up to set email alerts
|

Physicians, Clinics, and Neighborhoods: Multiple Levels of Influence on Colorectal Cancer Screening

Abstract: Background We 1) Described variability in colorectal cancer (CRC) test use across multiple levels, including physician, clinic, and neighborhood; and 2) Compared the performance of novel cross-classified vs. traditional hierarchical models. Methods We examined multilevel variation in CRC test use among patients not up-to-date with screening in a large, urban safety net health system (2011–2012). Outcomes included: 1) fecal occult blood test (FOBT) or 2) colonoscopy and were ascertained using claims data duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Notably, the neighborhood variability observed in our study persisted even after controlling for all covariates, including neighborhood poverty rate, indicating significant unexplained neighborhood variation in both outcomes. These results confirm a growing body of research suggesting that CRC outcomes, including screening, incidence, stage, and mortality, vary across geography [ 17 , 19 , 51 53 ]. For example, a prior study identified significant census-tract level variation in CRC survival that remained unexplained after accounting for individual covariates and neighborhood SES [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…Notably, the neighborhood variability observed in our study persisted even after controlling for all covariates, including neighborhood poverty rate, indicating significant unexplained neighborhood variation in both outcomes. These results confirm a growing body of research suggesting that CRC outcomes, including screening, incidence, stage, and mortality, vary across geography [ 17 , 19 , 51 53 ]. For example, a prior study identified significant census-tract level variation in CRC survival that remained unexplained after accounting for individual covariates and neighborhood SES [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…Studies could also include data about other contextual locations, including where individuals work and receive medical care. Multilevel research should consider the simultaneous influences of multiple levels, including clinic, hospital, physician, family, and neighborhood (26,27). Because neighborhoods also change over time, difference-in-difference models may allow for a better understanding of the impact of their dynamic nature on cancer etiology and outcomes (28).…”
Section: Future Opportunitiesmentioning
confidence: 99%
“…Statistical dimension reduction methods, such as principle component analysis and factor analysis, often are used to develop a single index or a set of factors to capture complex social environmental risk factors that are multidimensional in nature . Multilevel regression methods can be used to assess the impact of cancer risk factors that operate at different spatial scales . Because many cancer risk factors operate over an extended period, spatial‐temporal analysis methods are needed to assess exposure as individuals progress through daily travel and residential mobility …”
Section: Spatial Data For Cancer Researchmentioning
confidence: 99%
“…76 Multilevel regression methods can be used to assess the impact of cancer risk factors that operate at different spatial scales. 77,78 Because many cancer risk factors operate over an extended period, spatial-temporal analysis methods are needed to assess exposure as individuals progress through daily travel and residential mobility. 79 Types of spatial risk-factor data There are several important types of spatial data available for characterizing behavioral risk factors.…”
Section: Data Characteristicsmentioning
confidence: 99%